MEMBONGKAR KLAIM HARAM ATAS PENGHORMATAN BENDERA - Zainul Hakim (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2022)
Recently the extreme tendency in religion has strengthened (conservative turn). The online media also promoted the discourses and fatwas on prohibition and disbelief for Muslims to salute the Indonesian flag. This is also reinforced by some Muslim preachers who are indicated as part of the transnational Islamic movement (takfiri), which states that saluting the flag is a heresy (bid'ah) or haram. It can disrupt the unity and integrity of the Indonesian people (Bhinneka Tunggal Ika; unity in diversity). Therefore, this article seeks to reveal the meaning of flag-saluting from the perspective of Islamic studies, including aspects of taklifiy and wad'iy ways in Islamic law. This effort is carried out by searching rigidly, both lughowi and ma’nawi. The results of this study conclude that saluting the national flag is not included in the category of mahdhah worship. Therefore, it cannot be called heresy or shirk; moreover, the person who does it is called an apostate (murtad) or kafir (infidel). In such cases, honoring the flag based on ethics or moral behavior differs from worship based on theology. Thus, the article can help clarify and reflect on religious problems in society.